Air quality in Malaysia: Impacts, management issues and future challenges - Awang, Muhamad; Jaafar, Abu Bakar; Abdullah, Ahmad Makmom; Ismail, Marzuki; Hassan, Mohd Nasir; Abdullah, Ramdzani; Johan, Shamsuddin; Noor, Hamdan (2000)
Keywords: air quality;forest fire;haze;Malaysia;pollution Objective: Observations have been made on the long-term trends of major air pollutants in Malaysia including nitrogen dioxide, carbon monoxide, the ozone and total suspended particulate matter (particularly PM10), and sulfur dioxide, emitted from industrial and urban areas from early 1970s until late 1998.